Analysis of Sharia Commercial Banks in the Review of Maqashid Sharia with an Islamicity Performance Index Approach - Priyatno, Prima Dwi; Maulana, Agus; Darmastuti, Dewi; Agus Maulana (Journal of Islamic Economics and Finance Studies, 2024)
The development of Islamic banking continues to increase, growth in terms of assets and finance can also be said to be growing positively, but unfortunately the assessment or measurement of Islamic banking performance still uses the same instruments as conventional banking, even though Islamic banking has its own characteristics and principles. Therefore, the purpose of this study is to analyze the performance of Islamic banking with measurement instruments in accordance with the sharia maqashid method, measurement focuses on the benefits, namely the maintenance of religion, the maintenance of the soul, the maintenance of the offspring, the maintenance of the intellect, and the maintenance of the offspring. The method in this study uses a descriptive quantitative method with the Islamicity Performance Index model, the data used is secondary data from the financial statements of Islamic commercial banks in Indonesia. An analysis of various performance ratios of Islamic banks in Indonesia shows that PT. Bank Syariah Bukopin and PT. Bank Syariah Indonesia, Tbk stand out with high profit-sharing and zakat ratios, demonstrating a strong commitment to justice and fair distribution in line with syariah principles. PT. BPD West Nusa Tenggara Syariah excels in the Islamic Income Ratio, reflecting fully halal income. However, some banks, such as PT. Bank Tabungan Pensiunan Nasional Sharia, Tbk, and PT. Bank Aceh Syariah, display lower ratios in certain metrics, indicating the need for improvement in zakat distribution and halal income generation. Overall, this analysis underscores the importance of Islamic banks continually enhancing their adherence to syariah principles to achieve social justice and economic welfare in accordance with maqashid syariah.   Perkembangan perbankan syariah dari sisi aset dan keuangan tumbuh positif, namun sayangnya penilaian atau pengukuran kinerja perbankan syariah masih menggunakan instrumen yang sama dengan perbankan konvensional, padahal perbankan syariah memiliki karakteristik dan prinsip tersendiri. Tujuan penelitian ini adalah untuk menganalisis kinerja perbankan syariah dengan instrumen pengukuran sesuai dengan metode maqashid syariah, pengukuran berfokus pada kemaslahatannya, yaitu pemeliharaan agama, pemeliharaan jiwa, pemeliharaan keturunan, pemeliharaan kecerdasan, dan pemeliharaan keturunan. Metode dalam penelitian ini menggunakan metode kuantitatif deskriptif dengan model Indeks Kinerja Islamicity, data yang digunakan adalah data sekunder dari laporan keuangan bank umum syariah di Indonesia. Analisis terhadap berbagai rasio kinerja bank syariah di Indonesia menunjukkan bahwa PT. Bank Syariah Bukopin dan PT. Bank Syariah Indonesia, Tbk menonjol dengan rasio bagi hasil dan zakat yang tinggi, menunjukkan komitmen yang kuat terhadap keadilan dan penyaluran yang adil sejalan dengan prinsip syariah. BPD Nusa Tenggara Syariah Barat unggul dalam Rasio Pendapatan Islam, yang mencerminkan pendapatan halal sepenuhnya. Namun, beberapa bank, seperti PT. Bank Tabungan Pensiunan Nasional Syariah, Tbk, dan PT. Bank Aceh Syariah, menunjukkan rasio yang lebih rendah dalam metrik tertentu, menunjukkan perlunya perbaikan penyaluran zakat dan menghasilkan pendapatan halal. Secara keseluruhan, analisis ini menggarisbawahi pentingnya bank syariah terus meningkatkan kepatuhan mereka terhadap prinsip-prinsip syariah untuk mencapai keadilan sosial dan kesejahteraan ekonomi sesuai dengan maqashid syariah.